Determining factors of observance of antiretroviral treatments in Cameroon during the start-up period (2000-2002) - Commeyras C; Rey JL; Badre-Sentenac S; Essomba-Ntsama C (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Objective: highlight the socioeconomic and environmental determining factors of long-term observance to antiretroviral treatments in developing countries. Method: The regularity of antiretroviral prescriptions renewal at the central pharmacy of the Yaounde Central Hospital (Cameroon) was measured through analysing the medical and pharmaceutical files of 230 patients over the 21 month start-up period. 99 patients were also interviewed during the last six months. The determining factors were analysed according to various socio-economic criteria, linked with the longitudinal study of treatment observance. Results: The huge price decrease of HIV treatments during the start-up period was conducive to an increase in new treatments by a factor 5.76. In this context of an exploding demand, the paper shows that observance is firstly dependent on quality information about illness and treatment protocols, while longer term adherence is partly dependent on financial capability, and includes the strong influence of living conditions and behaviours. Conclusion: The paper recommends the introduction of free treatment as an objective in national sector policies and the organisation of a long term following-up of patients. In the African context of poverty and actual decentralisation of healthcare, the question of the availability of human resources is profoundly enhanced.